Bengali Steganography using CALP with a Novel Bengali Word Processor - Bhattacharyya, Souvik (2011)
Recent years have witnessed the rapid development of the Internet and telecommunication techniques. Steganography is the art and science of communicating in a way which hides the existence of the communication. Considerable amount of work has been carried out by different researchers on steganography. In this work the authors propose a novel text steganography method for Bengali text generated through a new approach of Bengali text processor. Considering the structure of Bengali alphabet, secret message has been hidden through changing the pattern of Bengali alphabet letters. This approach uses the idea of structural and feature changing of the cover carrier which is visibly indistinguishable from the original to the human beings and may be modified for other India language also.